Mengukur Kesiapan Sumber Daya Manusia Institut Agama Islam Negeri Menuju Universitas Islam Negeri - Asnaini, Asnaini; Abdullah, Irwan; Fatimah, Fatimah; Novitasari, Riri (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2022)
The transfer of the status of Islamic religious universities has the aim that Islamic education has breadth in developing general science based on Islamic science. Among practitioners and activists, this is known as scientific integration. In addition, transformation (alih status) has a very significant impact on all sides. Especially human resources, the main thing is lecturers. This study analyzed the readiness of lecturers' human resources at I.A.I.N. Bengkulu. This study used primary and secondary data—mapping and analyzing the real data of lecturers both in quantity and quality. The results showed that I.A.I.N. Bengkulu has lecturers who are lacking in quantity and low in quality. To solve this problem, UIN FAS Bengkulu must have a roadmap for developing lecturer competencies. The roadmap is structured correctly and done consistently. During the first five years, I.A.I.N. Bengkulu became UIN FAS Bengkulu was strongly encouraged to focus on the development of lecturers and returned to be carried out consistently for the next five years. If it is not done, it will have an impact on the development of the institution in the next ten years.